Strategic decision-making model for the regional development of rural areas: A Serbian case study - Voza, Danijela; Arsic, Sanela; Nikolic, Djordje; Zivkovic, Zivan (Publishing House of Wroclaw University of Economics and Business, 2023)
Making decisions about the activities aimed at enhancing rural development often requires implementing a multidisciplinary approach and including the opinions and attitudes of several regional stakeholders. This paper proposes a hybrid SWOT-ANP model for selecting an optimal scenario to realise the vision for developing a rural area in Serbia. The four-phase decision-making approach applied in this paper consisted of the following elements: vision, strategic goals, SWOT analysis, and alternative scenarios. The results indicated that the most appropriate strategies for regional development of this rural area were those related to the more sustainable utilisation of natural resources. This model should be of significant help to decisionmakers when defining the main determinants of the future development strategy of any rural area.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 263-286
Keywords: rural area; regional development; SWOT analysis; ANP method; strategies